1965
DOI: 10.2307/3895488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fertilization on A Little Bluestem Community

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…A number of previous investigations have been concerned with fertilizing species that are important on the tallgrass prairie, such as little bluestem, Schizachyrium scoparium (White 1961, Dickinson 1964, Nixon and McMillan 1964, Reardon and Huss 1965, van Amburg and Dodd 1970, Rao et al 1973, Senter 1975, Waller et al 1975. In other instances, fertilizers have been added to the prairie and responses have been measured in terms of yield (Gay and Dwyer 1965, McMurphy 1970, Owensby et al 1970, Hyde and Owensby 1973, Dodd and Lauenroth 1979, species com-positional changes (Huffine and Elder 1960, Owensby eta!.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous investigations have been concerned with fertilizing species that are important on the tallgrass prairie, such as little bluestem, Schizachyrium scoparium (White 1961, Dickinson 1964, Nixon and McMillan 1964, Reardon and Huss 1965, van Amburg and Dodd 1970, Rao et al 1973, Senter 1975, Waller et al 1975. In other instances, fertilizers have been added to the prairie and responses have been measured in terms of yield (Gay and Dwyer 1965, McMurphy 1970, Owensby et al 1970, Hyde and Owensby 1973, Dodd and Lauenroth 1979, species com-positional changes (Huffine and Elder 1960, Owensby eta!.…”
Section: Introductionmentioning
confidence: 99%
“…In monoculture, increased levels of nitrogen did not affect the growth rate of S. scoparium [51]. Other studies indicated that added nitrogen increased the dry mass of S. scoparium [59]; and there is a suggestion that the response of S. scoparium to soil nitrogen may be water dependent [60]. In the current study, we found that increased soil depth (volume and concomitantly the amount or availability of soil resources) increased the dry mass of S. scoparium in monoculture from 20 g·plant −1 in 30 cm deep soil to 48 g· plant −1 in the deepest soil tested.…”
Section: Discussionmentioning
confidence: 92%
“…In monoculture, increased levels of nitrogen did not affect the growth rate of S. scoparium (see Wilson and Tilman, 2002). Other studies indicated that nitrogen did increase the dry mass of S. scoparium (Kalmbacher et al, 1993); and there is a suggestion that the response of S. scoparium to soil nitrogen may be dependent on water availability (Reardon and Huss, 1965). In the current study, we found that increased soil nutrients increased the dry mass of S. scoparium in monoculture from 1 g plant À1 at low soil resources to 3.5 g plant À1 at high soil resources.…”
Section: Discussionmentioning
confidence: 98%